If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 27 + -6x Reorder the terms: 3 + 6x = 27 + -6x Solving 3 + 6x = 27 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 3 + 6x + 6x = 27 + -6x + 6x Combine like terms: 6x + 6x = 12x 3 + 12x = 27 + -6x + 6x Combine like terms: -6x + 6x = 0 3 + 12x = 27 + 0 3 + 12x = 27 Add '-3' to each side of the equation. 3 + -3 + 12x = 27 + -3 Combine like terms: 3 + -3 = 0 0 + 12x = 27 + -3 12x = 27 + -3 Combine like terms: 27 + -3 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| 5x+8=-90x-9x | | 9(2x+12)+20-25=5(5x-3)+2-3 | | -2+2x=-3+13 | | 2p-2=8 | | 4y-7z=39 | | 6m+5=11 | | 300-10x=30x | | x^2*3x=3x^3 | | 4p+1=101 | | 0.16*((2.48-0.16*x)/0.2) | | [3x-2]=-16 | | 3o=9 | | -10(s+3)=-119 | | -12x-4=-x-81 | | 7(4s+9)=175 | | 3mx-1=m-3x | | 3cos(2x)+5sin(x)-4=0 | | 10=3-(x/10) | | 0=3-(x/10) | | 30=3-(x/10) | | -4-4X=-6+9X | | 300=3-(x/10) | | 19=17+2x | | 0=30-(x/10) | | x=30-(10/10) | | D^3-2D^2-3Dy=0 | | 18w+4= | | (3w+4)+(3w+4)= | | 4000/x=1.129 | | 3cos(2x)+5sin(x)=4 | | X-4/5=1/3 | | 15=60x-5y |